Underpinning Starch Biology with in vitro Studies on Carbohydrate-Active Enzymes and Biosynthetic Glycomaterials - O’Neill, Ellis C.; Field, Robert A. (Frontiers in Bioengineering and Biotechnology, 2015)
Starch makes up more than half of the calories in the human diet; it is also a valuable bulk commodity that is used across the food, brewing and distilling, medicines and renewable materials sectors. Despite its’ importance, our understanding of how plants make starch, and what controls the deposition of this insoluble, polymeric, liquid crystalline material remains rather limited. Advances are hampered by the challenges inherent in analyzing enzymes that operate across the solid–liquid interface. Glyconanotechnology, in the form of glucan-coated sensor chips and metal nanoparticles, present novel opportunities to address this problem. Herein we review recent developments aimed at the bottom-up generation and self-assembly of starch-like materials, in order to better understand which enzymes are required for starch granule biogenesis and metabolism.